A influência das atividades não agropecuárias na infraestrutura domiciliar e no acesso a bens de consumo nos domicílios rurais do nordeste e sul do Brasil - Mesquita, Daiane Felix Santiago (2021)
The increase in the contingent of rural residents in non-agricultural activities is a reality all over the Brazilian territory. The search for such activities occurs because rural families crave higher and more stable incomes. However, analyzing the effect of these activities merely from the point of view of income can generate only a partial understanding. In this sense, the objective of this thesis was to analyze the extent to which income from non-agricultural activities in the northeastern and southern rural areas materializes in improvements to household infrastructure and durable consumer goods, in the period from 2002 to 2015. In order to do so, this thesis was divided into three chapters. The analyses were based on the reprocessing of microdata from the National Household Sample Survey (Pesquisa Nacional por Amostra de Domicílios - PNAD), published by IBGE. The observation units were rural agricultural, pluriactive and non-agricultural households, of own accounts and employees, from the Northeast and South regions. To meet the objectives of each chapter, synthetically, four procedures were adopted: tabular analysis and analysis of growth rates of the time series; construction of an Index of Household Infrastructure and Durable Consumer Goods for rural households; and quantile regression. The results showed the growth in the number of rural Northeastern and Southern families practicing non-agricultural activities and also attested that the highest average income was earned by pluriactivity; however, it was non-agricultural income that contributed most to this result, in the two regions analyzed. Regarding social conditions, the non-agricultural families were those that had the greatest access to variables of household infrastructure and consumer goods; it is believed that this result is due to the potential of these activities to amplify the effects of public policies. However, a significant portion of these families still do not have access to some items of household infrastructure and consumer goods, which suggests that income alone cannot guarantee full access to such dimensions. In addition, the quantile regression showed that the impact of income was greater in the group of poorer rural families, regardless of the activity practiced and the region. Finally, the thesis calls attention to the incentive to non-agricultural activities as possible enhancers of public policies for home infrastructure (which also need to be expanded) and the greater access to durable consumer goods variables.